The Importance of Implementing Environmental Management Accounting in Manufacturing Companies in Indonesia - Saribu, Ardin Dolok; Erlina, Erlina; Muda, Iskandar; Putra, Adi Syah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research aims to determine how environmental management accounting is implemented and essential in manufacturing companies. Environmental management accounting has a vital role in mediating environmentally friendly innovation. The compliance aspect significantly affects the implementation of environmental management accounting. Environmental management accounting can help management to improve the company's environmental performance to support sustainable development. Therefore, manufacturing companies need to pay attention to the importance of environmental management accounting in creating environmentally friendly innovations and improving the company's environmental performance to support sustainable development. The research method used is qualitative, with the author conducting a literature study by collecting data from various articles and several research journals and then analyzing it in more depth related to the research. In this research, it was concluded that applying Environmental Management Accounting in companies has many benefits and relevance in sustainable business.